STUDY ON COST BENEFIT ANALYSIS OF HIBUSCUS ROSASINENSIS INHIBITOR ON MILD STEEL (International Journal of Food and Nutritional Sciences, 2022)
Corrosion in today’s era is one of the challenging issue in industry and if corrosion has to be be controlled then we need to find out an cost-effective resolution for the problematic. The life expectancy of appliances is determined from past experience and sales data. Improved corrosion design for appliances can increase their life expectancy. However, if improved corrosion protection would mean the use of more expensive components for the appliances, then consumers may not be interested. Hence Cost-benefit analysis is dignified for both the edges for corresponding inexpensive problems. The present paper deals with the corrosion cost benefit analysis estimation calculated with the corrosion current calculator by using the extract of Hibisucus rosasinensis. By the corrosion rate by using environment friendly inhibitor will be beneficial for the industry to tackle the problem of corrosion. The study proved that by using Hibisucus rosasinensis extract value for the higher concentration of 1.0 µl corrosion rate calculated was found to be 2.1 mpy which states approximately more than 90% of corrosion is inhibited and found to be very advantageous cost benefit to the Industries